2009
DOI: 10.1080/00958970802290649
|View full text |Cite
|
Sign up to set email alerts
|

Two 2-D copper(II) azido compounds: catena -poly[ di 1,1- azido, di N,O-(quinolinecarboxylato)(aqua)copper(II)] and 1-D catena -poly[ di N,N′-(quinoxaline)copper(II)nitrate]

Abstract: To cite this article: Alshima'a A. Massoud , Vratislav Langer , Lars Öhrstrom & Morsy A.M. Abu-Youssef (2009) Two 2-D copper(II) azido compounds: catena -poly[ di -µ 1,1 -azido, di -µ N,O -(quinolinecarboxylato)(aqua)copper(II)] and 1-D catena -poly[ di -µ N,N′ -(quinoxaline)copper(II)nitrate], Journal of Coordination Chemistry, 62:4, 519-530To link to this article: http://dx.We synthesized three copper(II) complexes with two structurally related polydentate ligands, quinoline-4-carboxylic acid (quCOOH) and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The results of this investigation revealed that the ligand, Cu(II), Ni(II) and Co(II) complexes possessed higher antimicrobial activity, although it was generally reported that free ligands shown lower activity than complexes [7][8][9]27,28]. Additionally, when all the antimicrobial MIC values were compared, the ligand and Cu(II) complex displayed the highest antimicrobial efficacy with MIC values ranging between 20-40 mg mL À1 .…”
Section: Mass Spectramentioning
confidence: 86%
“…The results of this investigation revealed that the ligand, Cu(II), Ni(II) and Co(II) complexes possessed higher antimicrobial activity, although it was generally reported that free ligands shown lower activity than complexes [7][8][9]27,28]. Additionally, when all the antimicrobial MIC values were compared, the ligand and Cu(II) complex displayed the highest antimicrobial efficacy with MIC values ranging between 20-40 mg mL À1 .…”
Section: Mass Spectramentioning
confidence: 86%